Frequency of Depressive Illness among Caregivers of Drug Addicted Patients - Muhammad Amin Khan, Naeem Amjad, Iram Qamar, Farrukh Sarrfraz, Muhammad Saifullah (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Addictions and mental sickness are among the foremost expensive diseases in the world, according to a Worldwide Burden of Illness research, but they often go unnoticed. There’s a coordinate correlation between substance use disorder (SUD) and destitute treatment compliance, course and result, more vagrancy, more unemployment, criminal offenses, suicide and more awful overall functioning among individuals with mental sickness. A few large epidemiological studies have been conducted in industrialized countries to look at the predominance of SUD among individuals with mental sickness Objective: To find out the frequency of depressive illness among carers of drug addicted patients Material and Methods Study design: Quantitative cross sectional Settings: Niazi welfare foundation teaching Hospital Sargodha Duration: Four months i.e. 1st January 2022 to 30th April 2022 Data Collection procedure: Cross sectional study was conducted on 100 patients. Each patient demographic profile was recorded. Psychiatrists and psychologists took the interview and explained the purpose of study. Caregivers of patients with drug addicted were rule out for anxiety and depression. Results: The total number of patients was 100 in which 82 were males and 18 females. BMI of the patients was 24.5+ 12.7 and the mean age was 35.5+ 7.5. Majority of the patients belong to poor socioeconomic status as 68%. The living area of patients are 45% in urban and 55% in rural. The patients having depression percentage is 84% and anxiety 80%. Conclusion: This study highlighted the findings that carers of patients who used psychoactive substances shown serious sadness. On the one hand, the seriousness of medication-related challenges is clearly connected to the advancement of uneasiness and discouragement to others. Keywords: Depression, Anxiety, Psychoactive, drug, Caregivers